Competative Advantages Issues On Customer Lifetime Value On Retailers Profitability’s / Abdul Manaf Bohari...[et al.] - Bohari, Abdul Manaf; Rainis, Ruslan; Marimuthu, Malliga (2010)
In today's competitive environment, it is critical to a retailer's survival to understand and monitor their business profitability, which is mainly containing various types of customer in the marketplace. Managing relationship with customer is one of important initiatives to enhance Customer Lifetime Value of customer, then for ensure the consistent profitability of firms, both short and long run of business operation. In fact, customer lifetime value is strategic issues in the world wide of business competition because it has major influence on retailer’s profitability. On the one hand, managing relationship with customer is one of important initiatives to ensure the consistent profitability of firms. However, on the others hand, it is not easy to manages the customer profitability because retailer need to struggle with the key issues regarding their customers. Thus, these papers highlight the competitive advantages issues on customer lifetime values, with specific reference to retailing sectors. The important of understanding this issue is because of emerging of economic meltdown all over the world that has grate impacts toward competitive advantages levels. At the end, suggestion was made on how to strengthening the retailing position by utilizing spatial information technology. Spatial information technology has ability in creating benefits to retailers that is for enhancing the business strategic advantages to bring new dimension on lifetime value management of retailers.